2018
DOI: 10.1021/acs.energyfuels.7b03560
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Experimental and Kinetic Modeling Study of Cyclopentadiene Pyrolysis in the Presence of Ethene

Abstract: A combined experimental and kinetic modeling study is presented to improve the understanding of the formation of polycyclic aromatic hydrocarbons at pyrolysis conditions. The copyrolysis of cyclopentadiene (CPD) and ethene was studied in a continuous flow tubular reactor at a pressure of 0.17 MPa and a dilution of 1 mol CPD/1 mol ethene/10 mol N2. The temperature was varied from 873 to 1163 K, resulting in cyclopentadiene conversions between 1 and 92%. Using an automated reaction network generator, RMG, we pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 78 publications
0
16
1
Order By: Relevance
“…For most of the ten pathways, the PESs reported by Mebel et al 51 were used in this work. The difference was the newly reported calculations for C 5 H 5 + C 5 H 5 recombination and C 5 H 5 + C 5 H 6 reaction, where previously published C 10 H 9 and C 10 H 10 PESs were combined and rates evaluated by Long et al, 60 and rates on the C 10 H 11 surface were calculated by Vervust et al 59 The first step to generating pressure-dependent kinetics of the ten pathways is to identify the PES that each pathway belongs to. There were multiple pathways sharing the same potential surface, and some species and elementary steps are in common.…”
Section: From First To Second Aromatic Ringmentioning
confidence: 87%
See 1 more Smart Citation
“…For most of the ten pathways, the PESs reported by Mebel et al 51 were used in this work. The difference was the newly reported calculations for C 5 H 5 + C 5 H 5 recombination and C 5 H 5 + C 5 H 6 reaction, where previously published C 10 H 9 and C 10 H 10 PESs were combined and rates evaluated by Long et al, 60 and rates on the C 10 H 11 surface were calculated by Vervust et al 59 The first step to generating pressure-dependent kinetics of the ten pathways is to identify the PES that each pathway belongs to. There were multiple pathways sharing the same potential surface, and some species and elementary steps are in common.…”
Section: From First To Second Aromatic Ringmentioning
confidence: 87%
“…(N1) Hydrogen abstraction acetylene addition (HACA) 52,53 sequences, 54,55 (N2) Addition of vinylacetylene to phenyl radical, 51,56 (N3) Recombination of two cyclopentadienyl radicals and the reaction of cyclopentadienyl with cyclopentadiene, [57][58][59][60] (N4) Reactions of propargyl radical with benzyl radical, 61 (N5) Addition of 1,3-butadiene to phenyl radical, 62 (N6) Conversion of indene or indenyl radical to naphthalene via methylation. 63 Four pathways for indene include: (I1) Reactions of phenyl radical with allene and propyne, 63 (I2) Reactions of propargyl radical with benzene and phenyl radical, 63 (I3) A reaction of benzyl radical with acetylene, 64 (I4) Reactions of phenyl radical with propene and allyl radical.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al computed some of the reactions of propyl-, butyl-, and pentyl- benzene radicals. Ring closure reactions are more documented in the literature than PM reactions. , In particular, Bauschlicher and Ricca computed the barriers and heats of reactions of the formation of tetralin compounds. Mebel et al calculated the temperature- and pressure-dependent rate constants involved in the formation of indene by ring closure and its conversion to naphthalene.…”
Section: Introductionmentioning
confidence: 99%
“…Speybroeck et al 11 performed ab initio calculations to analyze different cyclization pathways for butylbenzene radicals taking thermodynamic and kinetic aspects into consideration. Vervust et al 13 reported experimental and kinetic modeling of indene and naphthalene formation. The kinetic parameters for ring closure of indane-type species were computed by Kislov et al, 4 and they were calculated by Guerra et al 2 at the CBS-QB3 level of theory for tetralin-type species.…”
Section: Introductionmentioning
confidence: 99%
“…Based upon the evidence from CH + pyrrole, the reaction of CH radical with cyclopentadiene (c-C 5 H 6 , CPD) could follow a similar ring expansion mechanism. With the identification of cyclopentadiene in the pyrolysis of several conventional fuels, the CH + cyclopentadiene reaction may be a route to benzene in combustion environments and other carbon-rich media.…”
Section: Introductionmentioning
confidence: 99%